The Muchina family: How dairy farming educate's Kenya's children - International Livestock Research Institute (International Livestock Research Institute, 2011)
The is the story about how keeping cows has enabled Margaret Muchina, a dairy farmer from central Kenya, to support and educate her four children, who include Edward Muchina who sat for his high school exam in 2010 and emerged as one of the country's best students.